The Fever Chart. Issue 1 (April 2020) - Kinsella, John
Abstract : 'The Fever Chart' is a new and extraordinarily timely novella by John Kinsella. Begun in late 2019 as the author was emerging from a prolonged bout of feverish 'flu, and finished in the first few weeks of 2020 during the peak of the catastrophic Australian bush fires, Kinsella describes the work as 'a storytelling "antifa" peace novella'. Responding to the climate activism of Greta Thunberg, and reacting against the attempts by industrialists and politicians at the 2020 World Economic Forum in Zurich to downplay the severity of climate change and biomic degradation, 'The Fever Chart' weaves a complex and compelling web of environmentally-attuned storytelling literary activism. Its publication during the feverish time of the COVID-19 pandemic is, ultimately, coincidental, but certainly no less relevant or significant for that.